Current antiseptics: a study on their antimicrobial activity and toxic effects on the corneal epithelium - O.A. Nazarchuk; I.L. Chereshniuk; G.G. Nazarchuk; D.V. Palii (Journal of Ophthalmology, 2019)
Background: Infectious agents can develop resistance to antibiotics, but antiseptics maintain their efficacy. It is still important to enhance our understanding of the effects of antiseptics on the macroorganism.